The Effect of Implementing Merdeka Curriculum on Teachers' Pedagogical Literacy Skills in Learning and Evaluation at Elementary Schools - Ma’muni, Sugeng; Suriswo, Suriswo; Nasukha, Muntoha (Journal of English Language and Education, 2025)
The objectives of the study were (1) to find out the success of the implementation of the independent curriculum, (2) to find out how much influence it has in improving teachers' pedagogical literacy in learning and (3) how much influence it has in improving teachers' pedagogical literacy in evaluation in public elementary schools in Margasari sub-district. The approach in this study uses a quantitative approach whose data relate to numbers. The design in this study aims to describe the extent of the influence of the implementation of the Merdeka curriculum in improving teachers' pedagogical literacy in learning and evaluation in elementary schools in Margasari Subdistrict.The population in this study were all public elementary school teachers in Margasari Subdistrict, Tegal Regency, totaling 43 teachers. Based on the results of data analysis and the results of hypothesis testing that have been revealed in the previous section, the results of the study include: (1) The effect of the implementation of the Merdeka Curriculum of State Elementary Schools in Margasari District, on this variable obtained an average of 3.20 with a good category (2) The effect on teacher literacy skills on a) Learning obtained an average of 3.25 with a good category b) Evaluation obtained an average score of 3.23 with a good category. (3) supporting factors for the implementation of the Independent Curriculum (a) supportive government policies, (b) school readiness, and (c) stakeholder involvement. Meanwhile, the inhibiting factors for the implementation of the independent curriculum in public elementary schools in Margasari Subdistrict: (a) lack of teacher understanding, (b) limited facilities and infrastructure, (c) challenges in implementing learning.